Magnetic compass of birds is based on a molecule with optimal directional sensitivity. - Ritz, T; Wiltschko, R; Hore, P; Rodgers, C; Stapput, K; Thalau, P; Timmel, C; Wiltschko, W (2009)
The avian magnetic compass has been well characterized in behavioral tests: it is an "inclination compass" based on the inclination of the field lines rather than on the polarity, and its operation requires short-wavelength light. The "radical pair" model suggests that these properties reflect the use of specialized photopigments in the primary process of magnetoreception; it has recently been supported by experimental evidence indicating a role of magnetically sensitive radical-pair processes in the avian magnetic compass. In a multidisciplinary approach subjecting migratory birds to oscillating fields and using their orientation responses as a criterion for unhindered magnetoreception, we identify key features of the underlying receptor molecules. Our observation of resonance effects at specific frequencies, combined with new theoretical considerations and calculations, indicate that birds use a radical pair with special properties that is optimally designed as a receptor in a biological compass. This radical pair design might be realized by cryptochrome photoreceptors if paired with molecular oxygen as a reaction partner.